EMOTIONAL EXHAUSTION AND ACADEMICIANS’ MENTAL HEALTH: A CONCEPTUAL STUDY ON MALAYSIA-BASED ACADEMICIANS WITH RESILIENCE AS THE MODERATOR - Thiam Yong Kuek; I-Chi Chen (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Concerns regarding mental health among academicians have become increasingly prevalent, particularly as universities aggressively pursue global rankings such as Times Higher Education (THE) and QS. This intensified competitive environment places significant pressure on academicians to continually perform at high levels, often resulting in burnout that affect their mental health. Malaysia-based academicians are not exempt from this phenomenon; however, studies specifically addressing mental health and burnout among this group remain limited. This conceptual paper explores mental health issues among Malaysia-based academicians by examining emotional exhaustion, a critical dimension of burnout. Additionally, this paper proposes resilience as a potential moderator in the relationship between emotional exhaustion and overall mental health among Malaysia-based academicians. Future empirical research based on this conceptualization can guide university management in developing effective interventions and supportive frameworks to address and improve academicians’ mental health.